Analisis Kinerja Keuangan Daerah Tentang Pengelolaan Anggaran Pendapatan dan Belanja Daerah Pada Pemerintah Kabupaten Maluku Tenggara (Periode 2017-2020) - Ester Yuditawaty Refo; Stenly S.J Ferdinandus (Soso-Q : Jurnal Manajemen, 2021)
ABSTRACT Good management of APBD realization is an important indicator to achieve regional financial performance, and therefore each region strives to be able to manage APBD realization. These considerations are the basis for writing a challenge to analyze regional financial performance on the management of the APBD in the Southeast Maluku District Government. The quantitative descriptive method is the method used in this writing. Data related to the target and realization of the Regional Budget of the Southeast Maluku Regency Government in 2017 - 2020 are important data that is complemented by explanations from the leadership in the OPD as well as various regulations related to the APBD to complement regional financial performance withseveral regional financial ratios. The results obtained are that the achievement of the regional financial independence ratio of Southeast Maluku Regency in 2018 to 2020 is low so that the first hypothesis can be proven. The results of the calculation of the regional financial dependence ratio of the Southeast Maluku Regency in 2018 to 2020 are high so that the second hypothesis can be proven. The results of the calculationof the efficiency and effectiveness ratio of the realization of Southeast Maluku Regency's Original Regional Revenue from 2018 to 2020 are effective and efficient so that the third and fourth hypotheses can be proven. The results of the calculation of the activity ratio in the form of the ratio of non-capital expenditures and capital expenditures in Southeast Maluku Regency from 2018 to 2020 are less satisfactory so that the fifth hypothesis can be proven. The results of the calculation of the growth/development ratio of the Southeast Maluku Regency Regional Budget from 2018 to 2020 are very volatile, which makes hypothesis six proven. The Regional Financial Performance of Southeast Maluku Regency in 2018 to 2020 is not good and this situation is in accordance with what is stated in the seventh hypothesis. Keywords: Regional Budget Management => Regional Financial Performance Analysis =>Regional Financial Performance